Modifikasi Struktur Gedung Menara Parkson Menggunakan Struktur Baja dengan Sistim Rangka Bresing Eksentrik - Aniendhita Rizki Amalia; Deded Eka Sahputra (Civil Engineering Collaboration, 2022)
Parkson tower is A Office building which is located in Bintaro Jaya, Tangerang Selatan. Singer Building on the design of reinforced concrete structures, which consists of 11 Floors, High with + 45m, plus 4 Floor basement, which functioned as a regional Parking, with depth of 12 m below the ground surface. The new building is planned to Parkson Tower will be built in the city of Padang, West Sumatra. As we know that the area is a with Padang earthquake zone High The need to review the design spesial Building. The building will be modified with Adding Period Of Building Floor 11 Floor 15 Floor And Being The previous basement Being Land Parking The function will be eliminated, because the land will be transferred Into Parking area beside the building, with Parking Broad availability of land. In the Thesis singer made repeated using a steel structure Eccentrically Braced Frames (EBF), Type wear bresing inverted V. Eccentrically Braced Frames (EBF) is a System Frame with stiffener beams and columns, where at any Edge Of stiffener connected to the review isolated Part of the beam so-called Link. on EBF, the weakest link is a part. So Failure on each on or collapse Structural damage to Happen works of human son on Link. Concept design EBF Link is established as part of Yang would Damaged, elements while lying elastic Conditions Remain hearts. Final Destination Of The singer is generating Planning Structural steel building includes Planning beam, beam Son, concrete filled steel tube column, Profile Link EBF, Profile bresing And Foundations That meets the requirements of Security Structures based SNI 03-2847-2013, SNI 03-1729 -2002, SNI 03-1726-2012, Dan PPIUG 1987